Fundraising Waqf at Micro Waqf Banks in Realizing People's Welfare - Arivatu Ni'mati Rahmatika; Silviana Rini (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2021)
Waqf has enormous potential in helping to realize the welfare of the people. Waqf is included in the category of muamalah teachings where the recommendation to implement it is sunnah. The realization of community welfare which is the main goal of waqf can be realized if waqf is managed in a productive way. Productive management of waqf funds certainly cannot be separated from the existence of waqf fundraising. This study aims to determine how waqf fundraising at Micro Waqf Banks. The type of research in this study used a qualitative type of research using descriptive methods. Sources of data needed to assist research obtained through primary and secondary data. The process of collecting data in this study was obtained through observation, interviews, and documentation. Furthermore, data analysis is carried out through several stages which include data reduction, data presentation, and then drawing conclusions and verification. The results showed that the fundraising of waqf in the Micro Waqf Bank Bahrul Ulum Barokah Sejahtera Tambakberas Jombang was obtained from LAZNas (National Zakat Amil Institution) then the funds were managed and distributed productively by the Micro Waqf Bank in the form of business loans with a group system to the community around the pesantren.